2014
DOI: 10.1371/journal.pone.0110250
|View full text |Cite
|
Sign up to set email alerts
|

Action Possibility Judgments of People with Varying Motor Abilities Due to Spinal Cord Injury

Abstract: Predictions about one's own action capabilities as well as the action capabilities of others are thought to be based on a simulation process involving linked perceptual and motor networks. Given the central role of motor experience in the formation of these networks, one's present motor capabilities are thought to be the basis of their perceptual judgments about actions. However, it remains unknown whether the ability to form these action possibility judgments is affected by performance related changes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 20 publications
2
14
2
Order By: Relevance
“…After the vision, participants had to report via keyboard the shortest time in which they and a young adult could accurately perform these movements. The SCI responses were consistent with their actual performance, with worse judgments in participants with cervical lesions as compared to those with below cervical SCI (Manson et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…After the vision, participants had to report via keyboard the shortest time in which they and a young adult could accurately perform these movements. The SCI responses were consistent with their actual performance, with worse judgments in participants with cervical lesions as compared to those with below cervical SCI (Manson et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Studies on SCI support this notion. Although these patients often report that they walk in their dreams (Saurat et al, 2011 ), there is evidence indicating that paraplegic patients may suffer from a dramatic reduction in their motor imagery capacities (Alkadhi et al, 2005 ; Chen et al, 2016 ; Di Rienzo, Collet, et al, 2014a ; Di Rienzo, Guillot, et al, 2014b ; Hotz-Boendermaker et al, 2008 ; Scandola, Aglioti, Pozeg, et al, 2017b ) and in the discrimination of biological motion (e.g., the direction of ambulation of a point-light walker; Arrighi et al, 2011 ), even if they are aware of their motor deficits (Manson et al, 2014 ). Again, these disorders in action representation may be topographically specific, involving actions that would be executed by the paralysed below-lesion body parts but not those performed by the above-lesion body parts (Pernigo et al, 2012 ; Scandola, Aglioti, et al, 2019a ).…”
Section: How Residual Motor Skills Following Sci Impact Cognitionmentioning
confidence: 99%
“…For example, prior to passing an object to a small child, we need to judge if the child can safely hold and maneuver the object. Previous studies have suggested that such action possibility judgments rely on a simulation process that utilizes linked action and perception networks [ 1 , 2 , 3 , 4 ]. Specifically, when asked to make a judgment about another person’s action, the actor first stimulates the action and forms a prediction about their own performance.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the use of simulations in action possibility judgments has emerged from studies examining the ability to predict MT based on movement difficulty [ 2 , 3 , 5 ]. Specifically, these studies used a Fitts’s Law paradigm that characterizes the relationship between MT and movement difficulty for reciprocal upper-limb reaching movements [ 2 , 3 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation